Dance and the Embodied Social Cognition of Mating: Carlos Saura’s Tango in the Perspective of the Tie-Up Theory - Lucchi Basili, Lorenza; Sacco, Pier Luigi (Integrative psychological & behavioral science, 2025)
This paper analyzes Carlos Saura’s film Tango through the theoretical lens of the Tie-Up Theory to explore how fictional narratives can serve as laboratories for investigating the embodied social cognition of romantic relationships. The study shows how dance, particularly tango, functions both as subject matter and cognitive metaphor in representing the complex dynamics of couple formation and maintenance. The film’s meta-representational structure, combining the creation of a dance performance with the exploration of actual relationships, reveals how cultural forms serve as cognitive scaffolds for understanding complex social dynamics. The study contributes to our understanding of how artistic representation can reveal typically implicit aspects of relationship cognition by demonstrating the value of integrating multidisciplinary perspectives of cognitive theory, psychology of mating, and cultural theory.